2004
DOI: 10.1182/blood-2003-05-1412
|View full text |Cite
|
Sign up to set email alerts
|

JNK activation is a mediator of arsenic trioxide-induced apoptosis in acute promyelocytic leukemia cells

Abstract: Arsenic trioxide induces c-jun N-terminal kinase (JNK) activation and apoptosis in acute promyelocytic leukemia (APL), where it has major clinical activity, but whether JNK is necessary to induce apoptosis is unknown. To clarify this necessity, we established 2 arsenic trioxide (As(2)O(3))-resistant subclones of the APL cell line, NB4. Both resistant lines showed little activation of JNK1 following treatment with As(2)O(3), even at doses sufficient to elicit robust activation in NB4 cells. One mechanism of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 34 publications
9
114
0
Order By: Relevance
“…[29][30][31] Davison et al also suggested that activation of the JNK pathway correlates with reversal of drug resistance by showing a temporal association of L-buthionine-[S,R]-sulfoximine treatment, JNK activation and sensitization of arsenic trioxide-resistant NB4 acute promyelocytic leukemia sublines to arsenic. 32 We evaluated our in vitro results in bone marrow cells obtained from AML patients before chemotherapy and confirmed the hypothesis that chemoresistance may be attributed to failure of JNK activation. We monitored the dynamic changes of phospho-JNK levels of primary leukemic cells after their in vitro exposure to anthracyclines.…”
Section: Discussionsupporting
confidence: 62%
“…[29][30][31] Davison et al also suggested that activation of the JNK pathway correlates with reversal of drug resistance by showing a temporal association of L-buthionine-[S,R]-sulfoximine treatment, JNK activation and sensitization of arsenic trioxide-resistant NB4 acute promyelocytic leukemia sublines to arsenic. 32 We evaluated our in vitro results in bone marrow cells obtained from AML patients before chemotherapy and confirmed the hypothesis that chemoresistance may be attributed to failure of JNK activation. We monitored the dynamic changes of phospho-JNK levels of primary leukemic cells after their in vitro exposure to anthracyclines.…”
Section: Discussionsupporting
confidence: 62%
“…1C), so 5 M of arsenite treatment was used as a negative control in the following studies. It may be noticed that the cytotoxicity of arsenite to cells is dependent on the forms of arsenite used (25,26) and cell types as well as species (27,28). For example, the cytotoxicity as well as cellular biological effects of arsenic trioxide and sodium arsenite are quite different when they are compared at the same concentration, which has been observed from the findings of various laboratories (5,10).…”
Section: Resultsmentioning
confidence: 58%
“…15 Therefore, we asked whether the activation of JNK might play a role in darinaparsin-mediated apoptosis in NB4 cells. First, we assessed JNK activation using an immune complex assay with GST-c-jun as an exogenous substrate.…”
Section: Jnk Activation Mediates Apoptosis Induced By Both As 2 O 3 Amentioning
confidence: 99%
“…Using pharmacologic and genetic approaches, we and others demonstrated that c-Jun NH 2 -terminal kinase (JNK) activation is required for As 2 O 3 -induced apoptosis in several malignant cell lines, including the APL cell line NB4. 14,15 As 2 O 3 has been investigated in the treatment of non-APL malignancies. 16,17,18 However, most of these studies showed substantially reduced antitumor effects of clinically achievable levels of As 2 O 3 , compared with those seen in APL.…”
Section: Introductionmentioning
confidence: 99%